2006
DOI: 10.1182/blood-2006-02-004572
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide therapy in myelofibrosis with myeloid metaplasia

Abstract: We present results of 2 similarly designed but separate phase 2 studies involving single-agent lenalidomide (CC-5013, Revlimid) in a total of 68 patients with symptomatic myelofibrosis with myeloid metaplasia (MMM). Protocol treatment consisted of oral lenalidomide at 10 mg/d (5 mg/d if baseline platelet count < 100 ؋ 10 9 /L) for 3 to 4 months with a plan to continue treatment for either 3 or 24 additional months, in case of response. Overall response rates were 22% for anemia, 33% for splenomegaly, and 50% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
140
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 238 publications
(147 citation statements)
references
References 37 publications
1
140
0
6
Order By: Relevance
“…Thus, a wait-and-see approach is often adopted in asymptomatic patients, delaying treatment start until a change in the clinical situation is observed. In patients with anemia, besides transfusion therapy, treatment is based on the use of androgens [19,20], erythropoietin or erythropoietin-stimulating agents [17,18] and, more recently, immuuomodulatory drugs such as thalidomide, lenalidomide or pomalidomide [21][22][23]. With regard to symptoms of hyperproliferation of MF, they are usually managed with oral cytoreductive drugs, mainly HU [9,10], but also busulfan [24] or melphalan [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a wait-and-see approach is often adopted in asymptomatic patients, delaying treatment start until a change in the clinical situation is observed. In patients with anemia, besides transfusion therapy, treatment is based on the use of androgens [19,20], erythropoietin or erythropoietin-stimulating agents [17,18] and, more recently, immuuomodulatory drugs such as thalidomide, lenalidomide or pomalidomide [21][22][23]. With regard to symptoms of hyperproliferation of MF, they are usually managed with oral cytoreductive drugs, mainly HU [9,10], but also busulfan [24] or melphalan [25].…”
Section: Discussionmentioning
confidence: 99%
“…2). First-line drugs of choice in such patients are hydroxyurea for symptomatic splenomegaly [125], androgens preparations [126], prednisone [126], danazol [127], thalidomide 6 prednisone [128][129][130] or lenalidomide 6 prednisone [131,132] for symptomatic anemia, splenectomy (or splenic radiotherapy for nonsurgical candidates) for splenomegaly that is resistant to conventional drug therapy [133], involved field radiotherapy for nonhepatosplenic EMH might and ruxolitinib for severe constitutional symptoms that are resistant to hydroxyurea therapy [133].…”
Section: Myelofibrosismentioning
confidence: 99%
“…Higher doses (100-400 mg/day) of thalidomide were associated with an increased adverse drop-out rate whereas low-dose (50 mg/day) thalidomide, alone or in combination with prednisone, was better tolerated and alleviated anemia in approximately 20% of treated patients with MF [5][6][7]. Lenalidomide (5-10 mg/day), with or without prednisone, also alleviated anemia in a similar proportion of patients with MF [3,8,9], and was most useful in the presence of del(5q) [10]. Two recent studies reassessed treatment response using the International Working Group for Myeloproliferative Neoplasms Research and Treatment (IWG-MRT) criteria [11]; one study reported up to 38% response rate for lenalidomide plus prednisone therapy [12] whereas the other study reported 28% response rate for thalidomide-based therapy [13].…”
Section: Introductionmentioning
confidence: 97%